PENINGKATAN LITERASI KESEHATAN MENTAL REMAJA MELALUI MEDIA KREATIF DI SMPN 11 SAMARINDA - Lujeng Rahayu Anggraini; Sarasmawati; Nabila Noor Alifa Basuki (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Mental health is a crucial aspect of student development, yet it is often overlooked in schools. Adolescents are vulnerable to academic, social, and emotional stress, requiring appropriate interventions to increase their awareness and ability to maintain their mental health. This study aims to improve adolescent mental health literacy through the use of creative media in the Leadership Project "Express Your Care: Mentally Healthy School Work." The method used was descriptive qualitative with a Project-Based Learning (PjBL) approach involving 10 students in grades VII and VIII. Data were collected through observation, documentation, participant reflection, and informal interviews during the implementation of three core activities: mental health outreach, poster design training using Canva, and screen-printing tote bags as a campaign medium. The results showed that the use of creative media proved effective in increasing students' understanding of mental health, developing design skills, and producing 10 campaign tote bags that were able to spread positive messages. These findings confirm that creative media can be a relevant and effective means of improving adolescent mental health literacy in schools